Leveraging AI for Nurturing Learners With Empathy, Ethics, and Social Responsibility - Rafeah, Wahi; Chuah, Kee Man; Syahrul Nizam, Junaini (IGI Global Scientific Publishing, 2026)
This chapter presents how leveraging artificial intelligence (AI) can create a transformative potential in fostering empathy, ethics, and social responsibility in higher education. It discusses the opportunities brought by AI technologies in enhancing both the emotional intelligence and social-emotional intelligence of learners by providing personalized support and developing empathy. While AI-driven tools offer personalised learning experiences that help in a deeper understanding of diverse perspectives, their adoption must be balanced so that technology enhances, not replace human-centric education. Accountability demands that institutions take responsibility for the consequences of the application of AI. Finally, the future of AI in values-based education depends on whether it can complement human educators by upgrading learning without compromising any core human element of teaching. Thoughtful and ethical adoption of AI will allow higher education to prepare learners as responsible global citizens in a fast-growing world.